Evaluation of Job Satisfaction & Social Identity of Rural Indian Pharmacist - J, Vivek; R, Priya; P, Shubhi; R, Shilpi; S, Preeti; P, Ashuthosh; R, Yashumati; P, Nishant (Indian Journal of Pharmacy Practice)
Introduction: The present study was design to investigate the level of job satisfaction and social identity among the pharmacist working in rural area of India. Method: Prepared questionnaire for pharmacist job satisfaction (QPJS) was distributed in field survey on pharmacists working in different setting of rural province of India. All the data were analyze by SAS software version 16.0. Results: With a 30.7% responding rate of QPJS, analysis shows that there were 85.4% pharmacist further wanted to suggest pharmacy as a carrier option to their friends and relatives. Whereas, only 37.8% respondents were desperate to work as a pharmacist until retirement. Additionally 67.7% wanted to change their profession in context to improved higher salaries in other profession. Further, ramble in work load per week (77.5% respondent working > 40 hours per week) and low salary (64.6% respondent earning up to only 15000 rupees per month) is likely lead to dissatisfaction among pharmacists. In addition, 66% of pharmacists thought that they do not get astonishing status according to their level of education which they deserve by the society. Conclusion: Majority of the pharmacists having low job satisfaction with squat social identity. The most significant finding of our study is that qualification, type of pharmacy shop, employment type, marital status, average number of hours worked per week, counseling time, practice experience salary, patient behavior, profession image and working environment are closely linked with job satisfaction level. Nonetheless, job satisfaction might not be associated to certain demographic variables, such as age and gender
Keywords: Rural Pharmacists; practice setting; job satisfaction; field survey; Likert scale; QPJS